Pengaruh Information Quality Dan Ease Of Use Terhadap Customer Loyalty Yang Dimediasi Oleh E-satisfaction Pada Aplikasi Grab Di Kota Bandung - Islami, Qhaerani Nurul; Putra, Hariyadi Triwahyu (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The high dependence of society on transportation is a justification for continuing to build a transportation industry that meets the needs of modern society. This study aims to analyze the effect of information quality and ease of use on customer loyalty mediated by e-satisfaction on the Grab application in Bandung City. Quantitative research type and primary data with questionnaire media then distributed using google form. Sampling was carried out using purposive sampling method with a sample of 100 respondents. With a population of men and women aged 17-50 years who have used the Grab application. The research instrument has gone through the validity and reliability test stages, classical assumption tests and multiple regression tests. The research explains that information quality and ease of use have a positive effect on customer loyalty mediated by e-satisfaction.